Public speaking competency analysis of Indonesian legislative in the first election part of Central Java - FITRI, DHEARAMA; Naryoso, S.Sos, M.Si, Agus (Interaksi Online, 2016)
This research was held to know and to evaluate public speaking competency of one of Indonesian Legislative members, Juliari Peter Batubara, with constituent research object who attended in recess in the first election part of Central Java. The method which be used is descriptive quantitative. The result of research showed that Juliari’s appearance looks tidy, with a fresh face, well dressed with matching suit, casual clothes and appropriate with theme of activity. Juliari could control his intonation, and has good tempo. Juliari has clear intonation and clear pronunciation. He used understandable analogy and language. The delivered material are actual, relevant with the audiences, complete with sample case, and give some supporting data from the speech. Juliari’s eyes contact is good and there is no over movement. Juliari did not utilize his body language in showing important point and his standing looks uncomfortable and seems awkward. The opening of his speech without giving a question, without shocking or interesting part, and there is no joke in it. Juliari gave and deliver some positive quotes to close his speech as an invitation. Juliari did not give joke in his speech like giving poetry in the beginning or end of his speech, closing with singing a song, or giving some jokes in his speech’s content when recess time in the first election part of Central Java. Based on this research, Juliari has good public speaking competency in some some aspects. The aspect which has not applied by Juliari in his speech is joke.